2015
DOI: 10.1002/aur.1521
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vocal Feedback to 9‐Month‐Old Infant Siblings of Children with ASD

Abstract: Infant siblings of children with autism spectrum disorder display differences in early language and social communication skills beginning as early as the first year of life. While environmental influences on early language development are well documented in other infant populations, they have received relatively little attention inside of the infant sibling context. In this study, we analyzed home video diaries collected prospectively as part of a longitudinal study of infant siblings. Infant vowel and consona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 50 publications
4
33
1
1
Order By: Relevance
“…The baseline regression model included only child communication as a predictor of parent responsiveness variables, due to replicated previous findings indicating associations between these two variables (Abraham et al, 2013; Leezenbaum et al, 2014; Talbott et al, 2015; Tamis-LeMonda et al, 2001; Wu & Gros-Louis, 2015). Subsequent variables were added to this baseline model, resulting in the following regression models: (a) child communication (as measured by either the CSBS-DP-CQ or the CSBS-DP-BS); (b) child communication and nonverbal cognitive level (as measured by the MSEL visual reception T score); (c) child communication and HYPO (as measured by either the SPA or SEQ); and (d) child communication and HYPER (as measured by either the SPA or SEQ).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The baseline regression model included only child communication as a predictor of parent responsiveness variables, due to replicated previous findings indicating associations between these two variables (Abraham et al, 2013; Leezenbaum et al, 2014; Talbott et al, 2015; Tamis-LeMonda et al, 2001; Wu & Gros-Louis, 2015). Subsequent variables were added to this baseline model, resulting in the following regression models: (a) child communication (as measured by either the CSBS-DP-CQ or the CSBS-DP-BS); (b) child communication and nonverbal cognitive level (as measured by the MSEL visual reception T score); (c) child communication and HYPO (as measured by either the SPA or SEQ); and (d) child communication and HYPER (as measured by either the SPA or SEQ).…”
Section: Resultsmentioning
confidence: 94%
“…Parents tend to respond more frequently to their infants with or without risk for ASD when the infant uses more sophisticated communication (Abraham et al, 2013; Karasik et al, 2014; Leezenbaum et al, 2014; Talbott et al, 2015; Wu & Gros-Louis, 2015). The current study supports these past findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studying these infants allows for the prospective study of ASD. Previous research has found relatively comparable early language environments of infants with and without a family history of ASD [Campbell, Leezenbaum, Mahoney, Day, & Schmidt, ; Northrup & Iverson, ; Swanson et al, ; Talbott, Nelson, & Tager‐Flusberg, ], while some subtle differences in the timing and synchrony of parent–child interactions have been reported [Northrup & Iverson, ; Wan et al, ]. Studies of older children with ASD showed that responsive caregiver language was associated with better joint attention and language skills [Bottema‐Beutel, Yoder, Hochman, & Watson, ; McDuffie & Yoder, ; Siller & Sigman, , ].…”
Section: Introductionmentioning
confidence: 99%